A 1.8 trillion degrees-of-freedom, 1.24 petaflops global seismic wave simulation on the K computer. (November 2016) - Tsuboi, Seiji; Ando, Kazuto; Miyoshi, Takayuki; Peter, Daniel; Komatitsch, Dimitri; Tromp, Jeroen
We present high-performance simulations of global seismic wave propagation with an unprecedented accuracy of 1.2 s seismic period for a realistic three-dimensional Earth model using the spectral element method on the K computer. Our seismic simulations use a total of 665.2 billion grid points and resolve 1.8 trillion degrees of freedom. To realize these large-scale computations, we optimize a widely used community software code to efficiently address all hardware parallelization, especially thread-level parallelization to solve the bottleneck of memory usage for coarse-grained parallelization. The new code exhibits excellent strong scaling for the time stepping loop, that is, parallel efficiency on 82, 134 nodes relative to 36, 504 nodes is 99.54%. Sustained performance of these computations on the K computer is 1.24 petaflops, which is 11.84% of its peak performance. The obtained seismograms with an accuracy of 1.2 s for the entire globe should help us to better understand rupture mechanisms of devastating earthquakes.